A study on information extraction from heterogeneous, distributed and autonomous dna databases using ontology-based agent - Samsudin, Ruhaidah; Othman, Muhamad Razib; Deris, Safaai; Md. Illias, Rosli (Faculty of Computer Science and Information System, 2005)

(untitled)
WWW is an information resource with virtually unlimited potential. However, this potential is relatively untapped because it is difficult for machine to process and integrate this information meaningfully. This is where the development of semantic web comes in, because unlike the existing WWW, where data is primarily intended for human consumption, the Semantic Web provides data that is also machine processable. Simple HTML Ontology Extension (SHOE), with its clear and efficient capabilities, is best applied in support the development of semantic web by allowing web authors to annotate their pages with machine-readable knowledge that can then be used by agents and query engines. Ontology-design methodology (Noy and McGuiness 2001) is a promising approach to demonstrate SHOE, since; all of SHOEs implicit knowledge arise from its use of ontologies. It is expected that this project will bring the web to its full potential, as well as expanding the application of SHOE in order to support the development of semantic web.